The jurisprudential and grammatical opinions of Ibn Asfour (d. (Journal of the College of Basic Education, 2023)
Praise be to God a lot, and prayers and peace be upon our master Muhammad and his family and those who appointed him until the Day of Judgment.Ibn Asfour - may God have mercy on him - is one of the scholars of Arabic. He has opinions and grammatical and personal interpretations that are unique to him, and they are many in his book (Dara’i al-Sha’ar).When presenting the issue he is discussing, the views of the grammarians are first presented before expressing his opinion on this issue, then he invalidates the opinion of this or that scholar or supports this or that scholar or is unique in his opinion when discussing a certain issue. Arabic scholars “have a position regarding the studies they tend to give, so they express their opinion by rejecting or affirming them at times, or not distinguishing and differentiating between what they want to clarify from the opinions, ideas, or issues that they raise in their research and writings at other times, so they attribute them to their owners without having an opinion.” ().When I read him in his book, I sensed a lot of grammatical opinions and jurisprudence, which he discusses and interprets, with support at times and opposition at other times, and without weighting.And I thought in dividing the research according to the jurisprudential opinions of Ibn Asfour according to his division of topics in his book, he divided it into four topics: first: the chapter of addition, second: the chapter of deficiency, third: the chapter of introduction and delay, fourth: the chapter of substitution.